A brief description of Madatya w.s.r to Alcohol poisoning -A Conceptual Study - Sharma, Durga Lal; Saini, Shri Ram (International Research Journal of Ayurveda & Yoga, 2021)
Alcoholism is a global health and societal concern that is on the rise. The stomach absorbs approximately 20% of the alcohol consumed. The remaining 80% is absorbed primarily through the small intestine. The circulatory also transports alcohol to the liver, which eliminates it from the bloodstream through a process known as "metabolising," in which it is transformed to a harmless chemical. The liver can only digest so much at a time, thus the remainder circulates throughout the body. As a result, the strength of the effect on the body is proportional to the amount consumed. When the amount of alcohol in the blood exceeds a particular threshold, the respiratory (breathing) system slows significantly, and oxygen no longer reaches the brain, resulting in a coma or death. Ayurveda classifies acute alcoholism, chronic alcoholism, and alcohol withdrawal as Madhya (Alcohol), Mada Intoxication, Madatya (Alcoholism), and Panapkaram, respectively. Though Ayurveda addresses alcoholism, chronic toxicity, withdrawal, and treatment, the opinions and principles for diagnosis and treatment are fragmented and differ from book. An attempt is made to organise the existing Ayurvedic literature on Madya and treatment of Madatya in a way that is both easy to understand and rewarding in the realm of treatment.